Assessing research. Vol. II, The researchers' view - Wooding, Steven; Grant, Jonathan; RAND Europe; Rand Corporation; Higher Education Funding Council for England (Santa Monica, CA : RAND, 2004)
The Research Assessment Exercise is used to assess the quality of, and determine core government funding for, research carried out in UK universities. In 2002 this process was reviewed (http://www.ra-review.ac.uk). This report provided evidence for the review; it describes workshops that investigated the academic community's views of research quality and attitudes towards models of assessment. Nine facilitated workshops were held in December 2002, which involved 142 academics and research managers from throughout the UK. The report outlines the recurring themes and issues raised by the participants. Key findings were that the overwhelming majority of participants thought research should be assessed using a system based on peer review; that there was a strong desire for a system with clear rules and transparent procedures; and that there was a need for improved systems to assess inter- and multi-disciplinary research work.
Information on Participants -- Task 1 Results -- Task 2 Assessing the Four Basic Systems -- Hybrid Systems and their Implementation and Implications .
"May 2003."
"RAND Europe."
Cover title.
Includes bibliographical references.
Also available on the internet via WWW in PDF format.
Keywords: Peer review of research grant proposals -- Great Britain; Research -- Evaluation -- Methodology; Research -- Great Britain